Efficient Financing under Asymmetric Information - BRENNAN, MICHAEL; KRAUS, ALAN (Journal of Finance, 1987)
ABSTRACT This paper characterizes the conditions under which the adverse‐selection problem, which may prevent a firm from issuing securities to finance an otherwise profitable investment, may be costlessly overcome by an appropriate choice of financing strategy. The conditions are specialized when the information asymmetry may be characterized by either a first‐degree‐stochastic‐dominance or a mean‐preserving‐spread ordering across possible distributions of firm earnings. Possible financing strategies that resolve the information asymmetry are discussed, and the results are related to recent empirical findings concerning security issues.